Variable Late Holocene 14C Reservoir Ages in Lake Bosten, Northwestern China - Zhou, Kang’en; Xu, Hai; Lan, Jianghu; Yan, Dongna; Sheng, Enguo; Yu, Keke; Song, Yunping; Zhang, Jin; Fu, Pingqing; Xu, Sheng (Frontiers in Earth Science, 2020)
Radiocarbon (14C) dating has been widely used in paleoclimate reconstruction. However, the reliability of the 14C age in lake sediments is sensitive to the 14C reservoir effect, especially for a lake in arid regions. In this study, we evaluated the 14C reservoir ages under different hydroclimatic conditions over the past ∼2300 years in Lake Bosten, northwestern China, by comparing with different dating results and with multi-proxy indices of a vertical-down sediment core collected in this lake. The 14C reservoir ages during ∼1800 to 650 BP (a dry interval) are estimated to be approximately 1170 years older than those during ∼650–100 BP and those during 2200–1800 BP (wet intervals). We proposed that variation in 14C exchange rate between the dissolved CO2 in lake water and CO2 in the atmosphere, as well as the changing proportion of organic matter in the lake and the catchment, could have contributed to the variable 14C reservoir ages in Lake Bosten. The result of this study suggests that the 14C reservoir effect may be larger in dry periods than in wet periods in the arid/semi-arid area, which should be considered when establishing age models of lake sediment cores from these regions.